Associations of choline-related nutrients with cardiometabolic and all-cause mortality: results from 3 prospective cohort studies of blacks, whites, and Chinese. Issue 3 (8th January 2020) - Yang, Jae Jeong; Lipworth, Loren P; Shu, Xiao-Ou; Blot, William J; Xiang, Yong-Bing; Steinwandel, Mark D; Li, Honglan; Gao, Yu-Tang; Zheng, Wei; Yu, Danxia
ABSTRACT: Background: Choline-related nutrients are dietary precursors of a gut microbial metabolite, trimethylamine-N-oxide, which has been linked to cardiometabolic diseases and related death. However, epidemiologic evidence on dietary choline and mortality remains limited, particularly among nonwhite populations. Objectives: This study aimed to investigate the associations of choline-related nutrients with cardiometabolic and all-cause mortality among black and white Americans and Chinese adults. Methods: Included were 49, 858 blacks, 23, 766 whites, and 134, 001 Chinese, aged 40–79 y, who participated in 3 prospective cohorts and lived ≥1 y after enrollment. Cox regression models were used to estimate HRs and 95% CIs for cardiometabolic [e.g., ischemic heart disease (IHD), stroke, and diabetes] and all-cause deaths. To account for multiple testing, P values < 0.003 were considered significant. Results: Mean choline intake among blacks, whites, and Chinese was 404.1 mg/d, 362.0 mg/d, and 296.8 mg/d, respectively. During a median follow-up of 11.7 y, 28, 673 deaths were identified, including 11, 141 cardiometabolic deaths. After comprehensive adjustments, including for overall diet quality and disease history, total choline intake was associated with increased cardiometabolic mortality among blacks and Chinese (HR for highest compared with lowest quintile: 1.26; 95% CI: 1.13, 1.40 and HR: 1.23; 95% CI: 1.11, 1.38, respectively; both P -trend < 0.001); among whites, the association was weaker (HR: 1.12; 95% CI: 0.95, 1.33; P -trend = 0.02). Total choline intake was also associated with diabetes and all-cause mortality in blacks (HR: 1.66; 95% CI: 1.26, 2.19 and HR: 1.20; 95% CI: 1.12, 1.29, respectively), with diabetes mortality in Chinese (HR: 2.24; 95% CI: 1.68, 2.97), and with IHD mortality in whites (HR: 1.31; 95% CI: 1.02, 1.69) (all P -trend < 0.001). The choline–mortality association was modified by alcohol consumption and appeared stronger among individuals with existing cardiometabolic disease. Betaine intake was associated with increased cardiometabolic mortality in Chinese only (HR: 1.16; 95% CI: 1.08, 1.25; P -trend < 0.001). Conclusions: High choline intake was associated with increased cardiometabolic mortality in racially diverse populations.